Long-term follow-up of a case of posterior microphthalmos (PRSS56) with hyperautofluorescent retinal pigment epithelial deposits. Issue 1 (January 2022) - Sen, Piyali; Robson, Anthony G; Webster, Andrew R; Nicholson, Luke; Sivaprasad, Sobha; Hykin, Philip G
Purpose: To report a case of posterior microphthalomos (PM) related to PRSS56 gene mutation with long term follow up with multimodal imaging findings. Methods: Single retrospective case report. Results: A 43-year old male patient presented in 2009 with bilateral reduced vision. Clinical examination and multimodal imaging showed features consistent with posterior microphthalmos with prominent bilateral horizontal papillomacular retinal folds. Posterior pole hyperautofluorescent RPE deposits were present. Gradual worsening of visual acuity and rod and cone photoreceptor function more so on the left was demonstrated during the 8 years of follow up. Conclusion: Hyperautofluorescent RPE deposits may occur in patients with posterior microphthalmos and such patient's may experience only gradual disease progression over long term follow up.